A Survey of Sarmatian Molluscs of the “Trochus podolicus” Group (Gastropoda, Trochoidea) - Anistratenko, O.Yu.; Anistratenko, V.V. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2005)
The Middle to Late Miocene (Sarmatian) species of the “Trochus podolicus” group are a heterogeneous assemblage which is here divided in the Gibbula podolica group (6 species) and Calliostoma podolicoformis group (4 species), in the families Trochidae and Calliostomatidae, respectively. New data on the biostratigraphy of C. podolicoformis (Kolesnikov, 1935) and on the biogeography of G. laevigatopodolica (Kolesnikov, 1930), G. cordieriana (Orbigny, 1844), C. hommairei (Orbigny, 1844) and C. beaumontii (Orbigny, 1844) are given. A phylogenetic scheme reflecting the relationships of the species discussed here is proposed. Interpopulation differences for some species are described; they are interpreted as a result of palaeo-environmental differences between the Halician and Borysthenian Gulfs of the Sarmatian Sea. Средне–позднемиоценовые (сарматские) виды группы «Trochus podolicus» являются гетерогенным конгломератом видов, который подразделен здесь на группы Gibbula podolica (6 видов) и Calliostoma podolicoformis (4 вида) в составе семейств Trochidae и Calliostomatidae соответственно. Приведены новые данные по биостратиграфии C. podolicoformis (Kolesnikov, 1935) и биогеографии G. laevigatopodolica (Kolesnikov, 1930), G. cordieriana (Orbigny, 1844), C. hommairei (Orbigny, 1844) и C. beaumontii (Orbigny, 1844). Предложена филогенетическая схема, отражающая родственные связи обсуждаемых видов. Описаны межпопуляционные отличия некоторых видов; они интерпретируются как результат различия палеоэкологических условий в Галицийском и Борисфенском заливах Сарматского моря.